Penggunaan Ekstrak Bawang Putih (Allium sativum) Sebagai Bahan Alami Celup Puting terhadap Kualitas Mikrobiologis Susu Sapi Segar - Thomas Alfindo Naionoe; Paulus K. Tahuk; Theresia I. Purwantiningsih (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
This research was conducted at Claretian Benlutu dairy farm, Batu Putih District, TTS Regency for one month. This research consisted of 2 stages, namely 1 month of nipple dyeing and the second stage of testing the sample in the laboratory. The purpose of this study was to determine the effect of the use of garlic extract (Allium sativum) as a natural ingredient in the nipple on the microbiological quality of fresh cow's milk. In this study used 16 nipples from 4 dairy cattle. The experimental design used was a Completely Randomized Design of 4 treatments and 3 replications, with the treatment being R0 = commercial antisep solution as a control, R1 = concentration of garlic extract 20%, R2 = concentration of garlic extract 25% and R3 = concentration of onion extract white 30%. The variables observed in this study were reductase time and total bacteria. The results showed that the use of garlic extract (Allium Sativum) had the same effect as the commercial antisep solution seen from the time of bacterial and total bacterial reductase (P> 0.05). This is because garlic has anti-bacterial allicin which can inhibit bacterial growth. It can be concluded that garlic extract has the same ability as a commercial antisep solution in inhibiting the bacteria that causes mastitis in the nipples of dairy cows. Microbiological test results of 2 variables of milk use of garlic extract with a concentration of 20% are very optimal in the use of dairy milk nipple dyes in addition to inhibiting bacteria also saves costs in making garlic extract.